The Relocatable House - Case, J.; Spanbroek, Nancy (University of Art and Design, 2001)
This proposal, citing three regional Queensland vernacular buildings as case studies, will evaluate the social, environmental and architectural benefits of relocatable building stock.With the imperative for environmental responsibility, a recycling industry has emerged, manifesting itself in a variety of ways regionally. In Queensland, Australia, one of these manifestations is the "removal house" industry.The basis of this industry is the "Queenslander". Its' timber framed construction enables cost effective removal of a house from its' site and its' relocation to another site. This generates an exciting array of possibilities, encompassing cost and environmental benefits, architectural possibilities of improvement and reinterpretation, and historical continuity through reuse.The flexibility innate in this type of construction and the suitability for transportation allow for re-configuration to suit the new user and readaptation to a new site as illustrated by the three case studies.Perhaps future housing designs should consider similar structural themes allowing for the re-transportation and manipulation of homes to meet modern day needs?